Operationalizing Human Immunodeficiency Virus Cure-related Trials with Analytic Treatment Interruptions During the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Pandemic: A Collaborative Approach. (25th August 2020) - Peluso, Michael J; Dee, Lynda; Shao, Shirley; Taylor, Jeff; Campbell, Danielle; Collins, Simon; Gandhi, Monica; Johnston, Rowena; Deeks, Steven G; Sauceda, John A; Dubé, Karine
Abstract: Efforts to recognize and minimize the risk to study participants will be necessary to safely and ethically resume scientific research in the context of the ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. These efforts are uniquely challenging in the context of human immunodeficiency virus (HIV) cure clinical trials, which often involve complex experimental therapy regimens and perhaps analytic treatment interruption, in which participants pause antiretroviral therapy. In this viewpoint, we discuss our approach to reopening an HIV cure trial in this context, with a focus on key considerations regarding study design, informed consent and participant education, and study implementation. These recommendations might be informative to other groups seeking to resume HIV cure research in settings similar to ours. Abstract : Approach to reopening a human immunodeficiency virus–cure trial that includes an analytic treatment interruption in the context of the severe acute respiratory syndrome coronavirus 2 pandemic, with considerations regarding study design, informed consent and participant education, and study implementation.